Plane Wave Coupling to a Transmission Line Above Ground with Terminating Loads - Warne, L. K.; Campione, S.; Coats, R. S. (Advanced Electromagnetics, 2019)
This paper considers plane wave coupling to a transmission line consisting of an aerial wire above a conducting ground. Simple circuit models are constructed for the terminating impedances at the ends of the line including radiation effects. We consider the following load topologies: open circuit, short circuit, and grounded rods. Results from the transmission line model with these loads show good agreement with full-wave simulations.